A randomized study comparing conventional percutaneous nephrolithotomy versus check pyeloscopic percutaneous nephrolithotomy - Rohit Purwar; Vasudevan Thirugnanasambandam; Abdulrazack Mossadeq (Urology Annals, 2021)
Objective: The objective of this study is to compare the advantages of check-pyeloscopic percutaneous nephrolithotomy (CP-PCNL) over conventional PCNL (C-PCNL) in the management of renal calculi. Materials and Methods: All patients with renal calculi requiring PCNL who attended the department of urology in a tertiary care center from December 2016 to October 2018 were included in the study. The patients were randomized into two groups of 50 each. Each group underwent PCNL in a conventional or check pyeloscopic method, respectively. Results: A total number of complications were more in C-PCNL group comprising of two pelvic tears, 8 infundibular tears, 1 minor urothelial injury, 2 cases of bleeding lasting for more than 24 hours, while in CP-PCNL group, complications were less (comprising of 1 minor urothelial injury and 1 case of infundibular tear). Statistical analysis was used to compare both the groups, and the results were statistically significant (P = 0.027). Conclusion: Check pyeloscopy at the time of PCNL is a safe, effective, and economical technique. This study shows that the complications such as blood loss, urothelial injury, and postoperative pain are less when check pyeloscopy is done during PCNL.